Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian di DimDimSum Tlogorejo Semarang - Agitta, Stevanie Rabella; Rustian, Lita Apriani; Setiawan, Freddy Aldo (STIE Widya Manggala, 2025)
The purpose of this study was to determine the effect of product quality and price on purchasing decisions of food products at DimDimSum Tlogorejo Semarang. This study used a sample of 100 people. The analysis data technique that used is multiple linear regression analysis regression analysis. The results of this study shows that there is a positive and significant effect of variable product quality (X1) and variable price (X2) on purchasing decision (Y). The influence of product quality (X1) and price (X2) on purchasing decisions (Y) is 52.1%, while the remaining 47.9% is influenced by other variables not examined in this study.